2013
DOI: 10.1186/1478-4491-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Removing financial barriers to access reproductive, maternal and newborn health services: the challenges and policy implications for human resources for health

Abstract: BackgroundThe last decade has seen widespread retreat from user fees with the intention to reduce financial constraints to users in accessing health care and in particular improving access to reproductive, maternal and newborn health services. This has had important benefits in reducing financial barriers to access in a number of settings. If the policies work as intended, service utilization rates increase. However this increases workloads for health staff and at the same time, the loss of user fee revenues c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
(82 reference statements)
1
43
0
Order By: Relevance
“…There was evidence that this may be temporary, as some nurses suggested that quality issues in the public sector spurred the volume of patients in private facilities to return to what it was before the policy implementation. This finding is consistent with research in five other African countries that also found that high levels of utilization in public facilities were not sustained following removal of fees (McPake et al 2013). Furthermore, nurses alluded to a sense of injustice, not only at having not been consulted about the policy change, but also from being told that their work load will increase significantly without increasing their pay.…”
Section: First Of All [It Is] In the Constitution Itself The [New] supporting
confidence: 81%
“…There was evidence that this may be temporary, as some nurses suggested that quality issues in the public sector spurred the volume of patients in private facilities to return to what it was before the policy implementation. This finding is consistent with research in five other African countries that also found that high levels of utilization in public facilities were not sustained following removal of fees (McPake et al 2013). Furthermore, nurses alluded to a sense of injustice, not only at having not been consulted about the policy change, but also from being told that their work load will increase significantly without increasing their pay.…”
Section: First Of All [It Is] In the Constitution Itself The [New] supporting
confidence: 81%
“…Human resources are the critical elements for the functioning of peripheral health structures globally [27,28] and more importantly in resource-constrained settings of Nepal [29][30][31]. As has been established previously, human resources act as the first interface between the patients and the peripheral health centres [27].…”
Section: Health System Characteristicsmentioning
confidence: 99%
“…There are reasons to believe that changes in prices happened in conjunction with changes in quality of care and that the perceived quality of care diminished in the public sector. Indeed, in Zambia, the health financing reform took place against the backdrop of a critical shortage of health workers, which affected particularly remote and rural areas (Carasso, Lagarde, Cheelo, Chansa, & Palmer, ; McPake et al, ). As a result, it is possible that populations in rural areas would expect relatively low quality of services in the public sector after fees were removed, mitigating their valuation of these free services.…”
Section: Introductionmentioning
confidence: 99%